Incidence and prevalence of hamstring injuries in field-based team sports: a systematic review and meta-analysis of 5952 injuries from over 7 million exposure hours - Maniar, N.; Carmichael, D. S.; Hickey, J. T.; Timmins, R. G.; San Jose, A. J.; Dickson, J.; Opar, D. (British Journal of Sports Medicine, 2023)
Objective: This study aimed to systematically review and meta-analyse the incidence and prevalence of hamstring injuries in field-based team sports. A secondary aim was to determine the impact of other potential effect moderators (match vs training; sport; playing surface; cohort age, mass and stature; and year when data was collected) on the incidence of hamstring injury in field-based team sports.